Simultaneous measurement of β- decay to bound and continuum electron states - Ohtsubo, Takashi; Kluge, Heinz-Jürgen (Physical review letters, 2005)
We report the first measurement of a ratio λβb/λβc of bound-state (λβb) and continuum-state (λβc) β−-decay rates for the case of bare 207Tl81+ ions. These ions were produced at the GSI fragment separator FRS by projectile fragmentation of a 208Pb beam. After in-flight separation with the Bρ−ΔE−Bρ method, they were injected into the experimental storage-ring ESR at an energy of 400.5A MeV, stored, and electron cooled. The number of both the 207Tl81+ ions and their bound-state β−-decay daughters, hydrogenlike 207Pb81+ ions, were measured as a function of storage time by recording their Schottky-noise intensities. The experimental result, λβb/λβc=0.188(18), is in very good agreement with the value of 0.171(1) obtained from theory employing spectra of allowed transitions.
Im Titel ist das Minuszeichen hochgestellt
Gesehen am 06.03.2020